Characteristics Of Red Dragon Juice (Hylocereus polyrhizus L) with Different CMC Concentrations In Cold Storage - Dyah Avidatul Ilma Hadi; Dian Purbasari (Universitas Muhammadiyah Mataram, 2023)
Red dragon fruit (Hylocereus polyrhizus L) is a horticultural plant from the Cactaceae family that has a high sweetness level of around 13-15°Brix and a large water content of around 90%. Based on this, further processing is needed so that the nutritional value can be maintained and extend the shelf life. One way that can be done is to process it into fruit juice drinks. Dragon fruit juice is a form of diversification of fresh dragon fruit made into soft drinks through the process of squeezing or crushing the fruit with or without additional food ingredients. The obstacle that occurs during the process of making juice is the appearance of sediment when stored. Therefore, a stabilising agent is needed in the preparation of fruit juice to keep the solid particles evenly dispersed. The purpose of this study was to determine the characteristics of red dragon fruit juice and analyse the effect of CMC concentration and storage duration on the characteristics of red dragon fruit juice. The results of the characteristics of red dragon fruit juice on the observation variable of total soluble solids have a value range of 9.288-11.215 °Brix, pH has a value range of 5.147-5.573, viscosity has a value range of 57.644-91.22cP, stability has a value range of 32.81-50.78%, the level of brightness has a value range of 24.760-28.324, the level of redness has a value range of 9.619-18.394, the level of yellowness has a value range of -1.927-1.560.